HUBUNGAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA PEKERJA PT JAYA KONSTRUKSI PROYEK BINTARO JAYA XCHANGE 2 - Denisa Dewanto (2022)
Workers are an asset of a company, because competent workers will produce good performance so that the company will develop. In construction companies, worker performance can be affected by occupational safety and health. Factors from occupational safety and health such as supervision, safety of work equipment, and conditions of the work environment are known to have a relationship with worker performance. The purpose of this study was to determine the relationship between occupational safety and health with worker performance of PT Jaya Konstruksi Bintaro Jaya XChange 2 Project. The type of study used quantitative analytic with a cross-sectional design, The population of the study was 125 workers, with the samples used were 95 workers with purposive sampling collection technique. This study uses the Chi-square test. The result in this study showed that supervision (p-value 0.000), safety of work equipment (p-value 0,003), and conditions of the work environment (p-value 0,000) have a significant relatinship with worker performance. Therefore, workers are advised to maintain physical condition and social relations in the workplace.